Realism in L'Historie de Gil Blas de Santillane - Silva, Evaneide Araújo da (Lettres Françaises, 2009)
L'Histoire de Gil Blas de Santillane is a fictional autobiography dated from 1715 to 1747. In this period in France, the novel ( the most popular genre in the 18th century) shows traces from the ancient form of the chivalric romance. The artificial characterics of this type of narrative forced upon the novels and the repetition of their themes, which bored the readers, made some writers try to recover the verossimilitude found in the romance narratives. In the 18th century, some writers carried on with this realist tendency and among them is Alain René Lesage. In L’Histoire de Gil Blas de Santillane, Lesage shows his preference for an art turned to the observation of the critical reality in such a way that his literature, confirming this inclination to realism, is a panel of the reality found in the 18th century, not only in Spain, where the action takes place, but also in the European society of the period.